PENGARUH PEMBELAJARAN KOOPERATIF INFORMAL THINK PAIR SHARE BERBANTUAN SCHOOLOGY TERHADAP HASIL BELAJAR - Rakhmatul Ummah; Dwi Sulisworo; Dwi Sulisworo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This study aims to determine the impact of informal cooperative learning think pair share tehnique assisted by Schoology aplication on student achievement. This study uses reseach instruments, and data analysis isquantitative/statistical.this reseach is a quasi experimental study, the design model used is control group pre test post test design, reseach data was processed using covariance analysis (ANCOVA), the population of this study is student of SMA N 1 Sape Bima NTB, the reseach sample was taaken by random sampling, the sample used was Grade XI student. From this study, it was found that the implementation of informal coopperative learning think pair share tehnique assisted by Schoology had a significant effect to student achievement.Keywords: Schoology, Informal Cooperative learning, Think pair share, achivement.